2019
DOI: 10.1073/pnas.1820513116
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genome-wide allele-specific expression in hybrid rice and the implications on the genetic basis of heterosis

Abstract: Utilization of heterosis has greatly increased the productivity of many crops worldwide. Although tremendous progress has been made in characterizing the genetic basis of heterosis using genomic technologies, molecular mechanisms underlying the genetic components are much less understood. Allele-specific expression (ASE), or imbalance between the expression levels of two parental alleles in the hybrid, has been suggested as a mechanism of heterosis. Here, we performed a genome-wide analysis of ASE by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(187 citation statements)
references
References 48 publications
14
172
1
Order By: Relevance
“…Owing to more and more high‐profile omics data and functional genomics data (Sun et al ; Zhao et al ; Shao et al ), the heterosis related allelic variation, especially the key causative variation, could be excavated, but more challenges may fall over the decoding of regulation networks of the heterosis genes. Near‐isogenic lines for multiple important heterosis genes or the genome editing technology that mimics natural alleles need to be used to picture the developmental processes that underlie how the heterozygous states of genes play a role in gene regulation.…”
Section: Genetic Basis Of Heterosismentioning
confidence: 99%
“…Owing to more and more high‐profile omics data and functional genomics data (Sun et al ; Zhao et al ; Shao et al ), the heterosis related allelic variation, especially the key causative variation, could be excavated, but more challenges may fall over the decoding of regulation networks of the heterosis genes. Near‐isogenic lines for multiple important heterosis genes or the genome editing technology that mimics natural alleles need to be used to picture the developmental processes that underlie how the heterozygous states of genes play a role in gene regulation.…”
Section: Genetic Basis Of Heterosismentioning
confidence: 99%
“…In mouse, Pinter et al (2015) showed that 95% and 82% of the identified ASE genes in F1 hybrids and in a reciprocal cross were also with tissue specificity, respectively [54]. Two alleles in rice hybrids might play different role in different environmental conditions and developmental stages, a higher proportion of ASE genes in those hybrids showed inconsistent patterns [55]. In the current study, 22, 81 and 25 ASE genes were identified in samples from skeleton muscle, adipose and both sharing tissues, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…8a-c). 9 To phase Iso-Seq transcripts, we developed a new tool called IsoPhase. For each gene, we aligned all full-length reads to the gene region, and then called SNPs individually (currently, IsoPhase only calls substitution SNPs).…”
Section: Isoform Characterization In Maize B73 Ki11 and Reciprocal mentioning
confidence: 99%
“…Previously, ASEs were studied using short-read RNA-seq, which could quantify alleles at the SNP level but was unable to provide full-length haplotype information 8,9 . Third-generation sequencing technologies such as PacBio and Oxford Nanopore offer full-length transcript sequencing that eliminates the need for transcript reconstruction, and these methods have been widely adopted for genome annotations 10,11,12,13,14 .…”
Section: Introductionmentioning
confidence: 99%